PREVENTING EFFECT OF THE PESTICIDE IN FARMING SOCIETY AT BUAHAN VILLAGE, KINTAMANI, BANGLI - Sutarga, dr. I Made (Buletin Udayana Mengabdi; Vol 6 No 2 (2007): Volume 6 No.2 - September 2007, 2012)
Abtract In the year 2004 from the result of research of horticultura farmer, from 46 person who had been checked their blood cholinesterase found 17.4% suffering of poison pesticide, 56.5% their knowlage still less to manage pesticide and also 47.8% less behavior in conducting real correct spraying, self protector applied should be used. The purpose of this activity to give understanding to farmer that use pesticide in managing pesticide and also to see pesticide conten through inspection of periodical cholinesterase. On Oktober 2006 from result checking of cholinesterase enzyme from 39 farmers. Their blood sample found cholinesterase enzyme rate >50-75 with degradation egual to 25% or suffer light poisond equal 23%. Farmer behavior in using pesticide still less. That is why counselling and also society inspection of cholinesterase enzyme required to be level and in the event of poisoned hence require to be intervenced continually through counselling continually through counselling and is rejancent of society.